1999
DOI: 10.1086/314658
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for an Effect of the CCR5 Δ32/+ and CCR2b 64I/+ Mutations on Human Immunodeficiency Virus (HIV)‐1 Disease Progression among HIV‐1–Infected Injecting Drug Users

Abstract: The relationship between CCR5 and CCR2b genotypes and human immunodeficiency virus (HIV)-1 disease progression was studied among the 108 seroconverters of the Amsterdam cohort of injecting drug users (IDUs). In contrast to earlier studies among homosexual men, no effect on disease progression of the CCR5 Delta32/+ and the CCR2b 64I/+ genotypes was found, when progression to AIDS, death, or a CD4 cell count <200/microL was compared by a Cox proportional hazards model. Furthermore, CD4 cell decline (by a regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
(41 reference statements)
2
33
1
Order By: Relevance
“…Thorough documentation of the extended CCR2 and CCR5 haplotypes has suggested that stable CCR haplotypes, alone or paired as genotypes, may influence the course of HIV-1 infection differentially according to their racial distribution (20,21,52); if so, variations in genotype frequencies among populations could have a sizeable differential impact on the course and the burden of disease (21). Conflicting observations on CCR2-64I (3,14,15,20,24,27,35,51,64,68,74); on SDF1 (27,61,73,76), and on CX 3 CR1 effects (16,45) may attest to similar population-specific effects of chemokine receptor and ligand genes other than CCR5.…”
mentioning
confidence: 99%
“…Thorough documentation of the extended CCR2 and CCR5 haplotypes has suggested that stable CCR haplotypes, alone or paired as genotypes, may influence the course of HIV-1 infection differentially according to their racial distribution (20,21,52); if so, variations in genotype frequencies among populations could have a sizeable differential impact on the course and the burden of disease (21). Conflicting observations on CCR2-64I (3,14,15,20,24,27,35,51,64,68,74); on SDF1 (27,61,73,76), and on CX 3 CR1 effects (16,45) may attest to similar population-specific effects of chemokine receptor and ligand genes other than CCR5.…”
mentioning
confidence: 99%
“…CCR2-64I is common and found in 10% of Caucasians, 15% of African-Americans, 25% of Asians and 17% of Hispanics [50]. Epidemiologic studies by Smith et al first demonstrated the association of CCR2-64I with delayed HIV-1 disease progression [50], which was confirmed by most subsequent studies [73,98,99], but not by others [82,100,101]. CCR2-64I is not associated with reduced risk for HIV-1 infection [50].…”
Section: Variation In the Ccr2 Coding Regionmentioning
confidence: 94%
“…However, our recent study suggests that individuals with the combination of heterozygous CCR5-32 and P1 CCR5 promoter genotype (see below) are relatively resistant to HIV-1 transmission [74]. According to most reports [47-49, 55, 75-81] but not all [82,83], individuals with heterozygous CCR5-32 progress from HIV-1 infection to AIDS more slowly than persons with two normal CCR5 alleles.…”
Section: Introductionmentioning
confidence: 94%
“…In HIV-1-infected intravenous drug users, hemophiliacs and recipients of contaminated blood [2, 51, 52], no effect of CCR5 Δ32 on disease progression was observed, whereas a protective effect was observed among HIV-1-infected children [53, 54]. It remains to be established whether this is due to study design or whether the effect of CCR5 Δ32 is indeed dependent on risk group and transmission route.…”
Section: Host Genetic Factors In Hiv-1 Disease Progressionmentioning
confidence: 99%